Proposal of Critical Nutrient Levels in Soil and Citrus Leaves Using the Boundary Line Method - Antonio João de Lima Neto; Amanda Veridiana Krug; Jean Michel Moura-Bueno; Danilo Eduardo Rozane; William Natale; Jacson Hindersmann; Ana Luiza Lima Marques; Lincon Oliveira Stefanello; Daniéle Gonçalves Papalia; Gustavo Brunetto (Plants, 2025)
Establishing critical levels (CLs) and sufficiency ranges (SRs) for nutrients improves fertilizer recommendations and supports citrus yield and fruit quality. The objective of this study was to establish CLs, soil fertility classes, and leaf nutrient SRs for citrus. This study used data on the yield and nutrients of the soil and leaves, collected from 2016 to 2021, of commercial orange (Citrus sinensis) and tangerine (Citrus deliciosa) orchards in the Southwest and Metropolitan regions of the state of Rio Grande do Sul, in southern Brazil. The yield data were related to the soil attributes/leaf nutrient contents. From the models obtained from this relationship, soil fertility classes and leaf sufficiency ranges were established using the boundary line (BL) method. The appropriate classes are 5.1–5.6 for pH, 1.0–1.4% for OM, 65.8–129.0 mg dm−3 for P, 161.4–326.0 mg dm−3 for K, 0.9–1.4 cmolc dm−3 for Ca, 0.22–0.34, cmolc dm−3 for Mg, 1.9–2.9 cmolc dm−3 for SB, 4.5–5.8 cmolc dm−3 for CEC, and 40.6–53.2% for V. The appropriate ranges of leaf contents were as follows: 19.1–22.7 g kg−1 of N, 0.8–1.3 g kg−1 of P, 7.8–11.3 g kg−1 of K, 20.9–28.4 g kg−1 of Ca, 2.0–3.3 g kg−1 of Mg, 2.0–3.0 g kg−1 of S, 88.8–127.5 mg kg−1 of B, 28.3–73.6 mg kg−1 of Cu, 74.3–122.5 mg kg−1 of Fe, 55.7–89.3 mg kg−1 of Mn, and 10.9–15.6 mg kg−1 of Zn. The BL method made it possible to establish nutrient CLs using data from commercial orchards, which is not possible when using conventional approaches. The established norms will allow for a more precise definition of the real need for fertilizer application in citrus orchards.